Potential Use of Pyrolysis Char from Waste Polymers as a Reductant for Direct Reduction of Mill Scale - Yong-Woo Kim; Sun-Joong Kim (Energies)
Waste polymers composed of carbonaceous compounds can be converted into gases and oils by pyrolysis. Although pyrolysis char is generated continuously in the pyrolysis process, its high ash content limits its industrial application. In the present study, the use of pyrolysis char with a high ash content as a reductant for the reduction reaction of mill scale was investigated. The mill scale reduction behaviors were investigated by modifying the mixing ratio of oxygen in the mill scale and fixed carbon in the pyrolysis char at temperatures ranging from 1723 to 1873 K. The degree of reduction of molten iron oxide in the mill scale was obtained by measuring the amounts of CO and CO2 gases generated during the reduction reaction in an Ar gas atmosphere. The degree of reduction increased with temperature and mixing ratio of the mill scale and pyrolysis char. In this study, the maximum degrees of reduction of mill scale at 1873 K were 0.32 and 0.65 for C/O ratios of 0.77 and 1.33, respectively. Based on a comparison of the rate constants for the overall mill scale reduction reaction with the previous rate constants, the rate-determining step in the present study was assumed to be the insufficient agitation effects owing to the limited gas evolution of CO and CO2 caused by the low gases released during reduction resulting from the low initial carbon concentration. In addition, the potential use of pyrolysis char produced from the pyrolysis of waste materials composed of carbon compounds as an alternative carbon source was investigated.